Sanctuary of Apollo. Temple of Apollo and tall Pedestal of Prusias, King of Bytina (dedicated by the Aetolian Confederacy)
Tall stone pillar which once bore statue of Prusias (2nd c. BC) King of Bithynia (Asia Minor), fr SW